Enhancing quality of regulation through public consultation: a case study of local governments in Terengganu - Mohd Yazid Abdul Majid
Empirical study has indicated that a country that promotes less administrative burdens in the long run will increase productivity. In Malaysia, private businesses have complained that some regulators failed to either consult or have insufficient consultation with them before gazetting new regulation; resulting in some losses not only to the businesses but also to the government. In the Concurrent List of Federal Constitution both States and Federal governments are given equal power to impose necessary regulations that could result in overlapping of regulations, in particular when sufficient public consultation requirements have been ignored. What about local government (in Peninsular Malaysia)? The Local Government Act 1976 also recognises them to introduce regulation (By-Law) related to their jurisdiction. The objectives of the research are: (i) to identify whether existing rule making process used by LGs incorporates public consultation; and (ii) to recommend a structured rule making integrated with public consultation fi·amework for LGs in Terengganu. As the research is SCoping to LGs in Terengganu and the diagnosis of the case is limited to planning for development as stated in the Town Country and Planning Act 1976 and jurisdiction under Local Government Act 1976, the research has adopted a qualitative approach by using semi-structured questiolmaire to interview industry and local governments (LGs) in Terengganu. Malaysia Productivity Corporation has selected 4 states and Terengganu is among the pioneer state to implement Good Regulatory Practice as recommended by III" Malaysia Plan. Then a focus group discussion is established to validate existing rule making structure and to finalise a workable framework rule making embracing 'j'>,ublic consultation for all LGs in Terengganu. This research has confirmed that existing structure of rule making process is unique as they do not follow national structure on developing new regulation. /\ new public consultation framework which is a modified version of federal and Australia models is introduced for LGs in Terengganu to consider. The application of sufficient public consultation with businesses and other stakeholders could improve the quality of regulation in Terengganu. Ultimately it will reduce the cost of doing business in Terengganu and improve the utilisation of resources of local governments.